Association between interleukin-10 (IL-10) promoter polymorphisms and non hodgkin lymphoma in Malaysian population / Somayeh Fani - Fani, Somayeh (2011)
Non-Hodgkin Lymphoma is one of the malignant diseases that has the most rapidly increasing incidence in many countries. IL10 is a potent cytokine, which has been considered to be involved in pathogenesis of non-Hodgkin lymphoma. Furthermore allelic variations in the genes that has been implicated in inflammation, such as interleukin 10 are candidate risk factors for NHL. This study was been conducted as a case-control experiment on 320 patients with NHL, 285 clinically normal subjects for IL10-1082 G/A SNP and 312 patients with NHL, 284 clinically normal subjects for IL10-819 C/T SNP. After DNA extraction, Polymerase Chain Reaction (PCR) was carried out to amplify two promoter Single Nucleotide Polymorphisms (SNPs), IL10-1082 G/A (rs1800870) and IL10-819 C/T (rs1800871) of the IL10 gene. PCR products were subjected to BseRІ and MslІ for genotyping of the IL10-1082 G/A and IL10-819 C/T respectively by analyzing the Restriction fragment length polymorphism (RFLP) patterns. Hardy-Weinberg equilibrium (HWE) of the genotype distribution in control population was examined with chi-square test. Association of the two SNPs with NHL in each of the three main ethnic groups (Malays, Chinese, and Indian) in Malaysia was examined using Fisher‟s exact test under allelic, dominant inheritance and recessive models. Genotype and allele frequencies of IL10-1082 G/A and IL10-819 C/T in all controls were in HWE. The results have indicated that IL10-1082 G/A polymorphism was not associated with NHL incidence. Conversely IL10-819 C/T was associated with risk of NHL only in the Malay population under the allelic and dominant inheritance model (P=0.0235, P=0.0297 respectively). However, further studies with extended sample size are required in order to confirm the association between IL10-819 C/T and NHL in Malaysian Malays.